Maneio Animal: Relatório técnico sobre análise do efeito de blocos de ureia-melaço no ganho de peso em bovinos nos distritos de Xai-Xai e Chicualacuala - Benedito, T; Abdul, C; Aida, C; Olga, F (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
This experiment was conducted to study the effect of supplementary urea-molasses block on the performance of cattle reared by smallholders in Xai-Xai and Chicualacuala districts, Gaza province. Fifty-seven (57) indigenous cattle of between 129-248 kg were selected for this experiment. They were grouped into three treatments by randomization and the experiment was conducted for a period of 60 days. Group 1 was supplemented with locally produced urea-molasses nutritive blocks (BUML), group 2 with urea-molasses nutritive blocks, commercially acquired (BUMC) and group 3 was not supplemented. The study revealed that cattle with access to nutritive blocks, locally manufactured or commercially acquired, had an average daily weight gain of 556.1 or 553 g/day, respectively that was significantly more (P<0.05) than the control that only had an increase in weight of 98.6 g/day in Xai-Xai district. The same tendency was found in Chicualacuala, the live weight gain of cattle with access to locally manufactured or commercially acquired blocks was significantly higher (P<0.05) (337 or 443 g/day), respectively, than those not supplemented with nutritive blocks, that only increased their weight at a rate of 41.7 g/day. Comparing the daily weight gains between the two supplemented treatments, locally manufactured and commercially acquired nutritive blocks, (556.1 vs 553 g/d or 337 vs 443 g/dia), no significant differences were registered (P>0.05). It is concluded that urea-multi nutritive block can be used to improve the performance of cattle.